Application of ecological and mathematical theory to cancer: New challenges - Yangjin Kim; Avner Friedman; Eugene Kashdan; Urszula Ledzewicz; Chae-Ok Yun (Mathematical Biosciences and Engineering)
According to the World Health Organization, cancer is among the leading causes of morbidity and mortality worldwide. Despite enormous efforts of cancer researchers all around the world, the mechanisms underlying its origin, formation, progression, therapeutic cure or control are still not fully understood. Cancer is a complex, multi-scale process, in which genetic mutations occurringat a sub-cellular level manifest themselves as functional changes at the cellular and tissue scale.For more information please click the “Full Text” above.